2007
DOI: 10.1038/sj.cdd.4402208
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of hereditary inclusion body myopathy myoblasts: possible primary impairment of apoptotic events

Abstract: Hereditary inclusion body myopathy (HIBM) is a unique muscular disorder caused by mutations in the UDP-N-acetylglucosamine 2-epimerase/N-acetylmannosamine kinase (GNE) gene. GNE encodes a bi-functional enzyme acting in the biosynthetic pathway of sialic acid. Since the underlying myopathological mechanism leading to the disease phenotype is poorly understood, we have established human myoblasts cultures, derived from HIBM satellite cells carrying the homozygous M712T mutation, and identified cellular and molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 39 publications
(37 reference statements)
3
41
1
Order By: Relevance
“…Although we and others demonstrated that hyposialylation does exist in DMRV/hIBM cells, others reported that there is no overall hyposialylation in the myoblasts and lymphoblastoid cell line from DMRV/hIBM patients [Salama et al 2005;Hinderlich et al 2004]. In addition, GNE-gene product has been proposed to have functions and roles outside sialic acid biosynthesis [Amsili et al 2007;Wang et al 2006]. We also do not completely discount that there might be other factors that could contribute to the pathogenesis of DMRV/hIBM.…”
Section: Toxicology Of the Compoundsmentioning
confidence: 92%
“…Although we and others demonstrated that hyposialylation does exist in DMRV/hIBM cells, others reported that there is no overall hyposialylation in the myoblasts and lymphoblastoid cell line from DMRV/hIBM patients [Salama et al 2005;Hinderlich et al 2004]. In addition, GNE-gene product has been proposed to have functions and roles outside sialic acid biosynthesis [Amsili et al 2007;Wang et al 2006]. We also do not completely discount that there might be other factors that could contribute to the pathogenesis of DMRV/hIBM.…”
Section: Toxicology Of the Compoundsmentioning
confidence: 92%
“…The reactivities to lectins are also variable in some myofibers, suggesting that hyposialylation in muscles may contribute to the focal accumulations of autophagic vacuoles and/or amyloid deposits in affected muscle tissue. Although sialic acid dysregulation is likely primary to disease pathogenesis, recent assessments of myoblast cellular sialylation patterns,14,15 suggest the possible role of other GNE-related contributing mechanisms 54,55. Eisenberg et al looked at the role of GNE gene and other neighboring genes, such as, clathrin light chainA (CLTA)56 which is a regulatory element in clathrin gene function, known to be involved in several pathways of lysosomal proteolysis, and, reversion-inducing cysteine-rich protein with Kazal motifs (RECK)57 which is a membrane-anchored glycoprotein with transformation suppressor activity both located close to the GNE gene 58.…”
Section: Molecular Biologymentioning
confidence: 99%
“…The sialic acid modifications of cell surface glycoproteins are crucial for cell adhesion and signal transduction and may result in muscle fiber degeneration (Huizing, Hermos et al 2002; Vasconcelos, Raju et al 2002). Although sialic acid dysregulation is likely to significantly contribute to disease pathogenesis, recent assessments of myoblast cellular sialylation patterns suggest the possible role of other GNE related contributing mechanisms, such as GM3 and GD3 synthase regulation and impaired apoptosis signalling (Hinderlich, Salama et al 2004; Salama, Hinderlich et al 2005; Wang, Sun et al 2006; Amsili, Shlomai et al 2007). Additionally, recent developments in the field of GNE research has implicated the bifunctional enzyme to also play a role in functions other than sialic acid production.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, recent developments in the field of GNE research has implicated the bifunctional enzyme to also play a role in functions other than sialic acid production. These functions include cell proliferation, apoptosis, regulatory gene expression and modulatory sialytransferases (Wang, Sun et al 2006; Amsili, Shlomai et al 2007). …”
Section: Introductionmentioning
confidence: 99%